Temporal Trends of Persistent Organic Pollutants in Sarasota Bay Common Bottlenose Dolphins (Tursiops truncatus) - Kucklick, John; Boggs, Ashley; Huncik, Kevin; Moors, Amanda; Davis, Elizabeth; Ylitalo, Gina; McConnell, Mary; Makris, Christina; Wells, Randall S. (Frontiers in Marine Science, 2022)
Legacy persistent organic pollutants (POPs) were measured in blubber samples collected from 196 common bottlenose dolphins (Tursiops truncatus) from 2000 to 2016 in the Sarasota Bay, Florida, ecosystem. Legacy POPs included polychlorinated biphenyl congeners (SPCB; sum of 37 congeners or congener groups), DDT and transformation products (SDDT), chlordane and related compounds (SChlor), mirex, polybrominated diphenyl ether congeners (SPBDE, sum of five congeners), dieldrin and hexachlorobenzene (HCB). All POP compounds or compound groups declined in dolphin blubber over the study period. POPs classes declined at different rates within classifications (sex, adult or calf). For example, dieldrin decline in male dolphins was greatest (-13% per year) while HCB decline was lower (-6.3% per year). For individual POP classes, rates of decline depended on classification. For example, SPCB, the POP class present at the highest concentration relative to other POPs, declined at -8.4%, -7.8%, and -5.6% per year in adult females, adult males and calves, respectively. Overall POP declines were highest in adult males and lowest in calves. Declines in POP concentration with time based on individual dolphins resampled at different time points were consistent with declines calculated based on yearly or biennial cross-sections taken from 2000 through 2016. Overall rates of decline in Sarasota Bay bottlenose dolphins were like declines seen for Great Lakes fish and about twice the rate of decline observed in arctic temporal trend data sets. POP trends appear to have leveled off since 2009 in Sarasota Bay dolphins. For example, SPCBs in calves appear to have stabilized at 21 mg/kg lipid. Recent published work on delphinids with blubber concentrations spanning those observed in the present work suggest that levels of legacy POPs currently observed in Sarasota dolphins may suppress population growth. Results from this study confirm the need for continued monitoring of POPs in the Sarasota Bay bottlenose dolphin population to see if concentrations are continuing to fall or have indeed plateaued.